Free will and conformity: less faith in free will corresponds to greater tendency to conformism - V. G. Keller (Омский научный вестник: Серия "Общество. История. Современность")
Philosophical debates around the concept of free will have not ceased for many centuries. Modern discussions in moral philosophy are increasingly turning to new scientific discoveries of social psychology and neurobiology. On the wave of interest of modern moral philosophy for these scientific discoveries has arisen experimental philosophy. This article raises the question of the relationship between a person’s belief in free will and conformity. The study is based on the methods of experimental philosophy, in particular, the correlation between these two indicators is measured. The participants in our experiment filled in two scales assessing an individual’s faith in freedom of will and his tendency to conformism. The results of the experiment provided the evidence that respondents with stronger belief in free will showed a less tendency toward conformism